A methodology for knowledge representation in defeasible logic programming - Stankevicius, Alejandro G. (2006)
Humans have always been intrigued by their ability to reason. We have constantly attempted to emulate this process, trying almost everything, from physiological explanations, to sociological accounts. The approach with possibly the longest tradition conceives this process as a mere manipulation of symbols. Yet, symbolic reasoning cannot be applied directly over the problem at hand: we require that the knowledge about that domain be also described symbolically, where this description is in turn the outcome of the process called Knowledge Representation. Defeasible Logic Programming (DeLP) is a formalism that by combining Logic Programming with Defeasible Argumentation is able to represent incomplete and potentially contradictory information. Its ability to represent this kind of informartion make it suitable for describing many real world situations, where its inference engine can then later be used to solve concrete problems in those scenarios. In this article we propose a formal methodology, striving to standardize the process of knowledge representation in DeLP, that defines a set of guidelines to be used during this key task.